Overheating of residential buildings in the severe cold and cold regions of China: The gap between building policy and performance. (November 2022) - Bo, Rui; Chang, Wen-Shao; Yu, Yang; Xu, Yitong; Guo, Haibo
Abstract: Given the forecasts of global warming and heatwaves, concern is growing about the exacerbation of overheating in dwellings in severe cold and cold regions of China. This concern, however, has been neglected by Chinese national building codes and standards. The focus in these regions has been to preserve heat during winter, lacking in definite measures prescribed for heat protection during summer. Although many studies have examined the situations in Europe, limited effort has been devoted to investigating overheating in China. The aim of this research is to use validated simulation results and empirical data to reveal overheating risk in these regions of China and identify deficiencies in local standards. The indoor temperature of residential buildings in four representative cities (Yichun, Harbin, Shenyang and Dalian) was measured from May to September 2021. To extend the observation period and enhance the reliability of the results, this study carried out building performance simulations using typical weather data over 15 years (2004–2018). Having the models validated, the results revealed the severity of overheating phenomenon. During the summertime (May to September), overheating were recorded for 6, 191, 483 and 578 h out of total 3672 h (accounted for 0.4%, 12.4%, 31.6% and 37.6%) in the south-facing bedrooms of Yichun, Harbin, Shenyang and Dalian respectively. It is therefore suggested that the design standards should consider a trade-off between thermal retention in winter and overheating in summer. The findings provide useful information and guidance for policymakers contemplating low-carbon building schemes and regulations on thermal comfort. Highlights: Vast territory measurements in newly-built stocking of severe cold and cold regions in China. Simulation applied with local-recorded weather files of 2021, validated against monitoring results. Simulation applied with TMY weather files over a recent 15-year period, revealing typical overheating performance. Suggestions for modification of building regulations in the regions.